"I'm Getting Older Too": Challenges and Benefits Experienced by Very Old Parents and Their Children. (March 2022) - Boerner, Kathrin; Kim, Yijung K.; Gallagher, Elizabeth A.; Kim, Kyungmin; Jopp, Daniela S.
Very old parents and their "old" children are a growing group in industrialized countries worldwide. However, virtually nothing is known about the nature and implications of this relationship constellation. To fill this gap, this study explored the challenges and rewards of the very old parent–child relationship. In-depth interviews were conducted with 114 parent–child dyads (parent age ≥90; child age ≥65). While both challenges and rewards were present, the balance of challenges and rewards was notably less favorable for children with more challenges experienced overall. Challenges reported by children were often characterized by references to children's own advanced age and health problems, and the prolonged caregiving involvement due to their parents' longevity. Health care professionals, policymakers, and families should be made aware of this increasingly common phenomenon, and specific services and policies will be needed to adequately support very old adults and their families.